Qur’anic Interpretation of Dhikr and the Reconfiguration of Religious Authority in Digital Media - Aden Abdul Malik; Moh. Masrur (UIN Raden Mas Said Surakarta, 2025)
The rapid growth of digital da‘wah on YouTube has significantly transformed how Muslims engage with the Qur’an, repositioning the platform as a key site for religious interpretation and authority formation. This article examines how Qur’anic interpretation of dhikr contributes to the reconfiguration of religious authority in the digital sphere, focusing on the YouTube sermons of Ustadz Adi Hidayat (UAH). Employing a qualitative descriptive approach, the study integrates tafsir mawḍū‘ī (thematic exegesis) with critical discourse analysis to analyze sermon content and audience interactions in the comment sections. The findings demonstrate that UAH conceptualizes dhikr not merely as a verbal ritual, but as a comprehensive spiritual framework encompassing prayer, ethical discipline, and inner tranquility. Moreover, audience responses reveal the emergence of a digitally mediated “dhikr community” in which religious meanings are collectively interpreted and affirmed. This dynamic illustrates how YouTube functions as a space for Qur’anic meaning-making that reshapes traditional patterns of religious authority in contemporary Islam.